Adjunctive repetitive transcranial magnetic stimulation for adolescents with first-episode major depressive disorder: a meta-analysis - Sun, Chen-Hui; Mai, Jian-Xin; Shi, Zhan-Ming; Zheng, Wei; Jiang, Wen-Long; Li, Ze-Zhi; Huang, Xing-Bing; Yang, Xin-Hu; Zheng, Wei (Frontiers in Psychiatry, 2023)
Objective This meta-analysis of randomized clinical trials (RCTs) was conducted to explore the therapeutic effects, tolerability and safety of repetitive transcranial magnetic stimulation (rTMS) as an adjunct treatment in adolescents with first-episode major depressive disorder (FE-MDD). Methods RCTs examining the efficacy, tolerability and safety of adjunctive rTMS for adolescents with FE-MDD were included. Data were extracted by three independent authors and synthesized using RevMan 5.3 software with a random effects model. Results A total of six RCTs involving 562 adolescents with FE-MDD were included. Adjunctive rTMS was superior in improving depressive symptoms over the control group [standardized mean difference (SMD) = −1.50, 95% confidence interval (CI): −2.16, −0.84; I2 = 89%, p < 0.00001] in adolescents with FE-MDD. A sensitivity analysis and two subgroup analyses also confirmed the significant findings. Adolescents with FE-MDD treated with rTMS had significantly greater response [risk ratio (RR) = 1.35, 95% CI: 1.04, 1.76; I2 = 56%, p = 0.03] and remission (RR = 1.35, 95% CI: 1.03, 1.77; I2 = 0%, p = 0.03) over the control group. All-cause discontinuations were similar between the two groups (RR = 0.79, 95% CI: 0.32, 1.93; I2 = 0%, p = 0.60). No significant differences were found regarding adverse events, including headache, loss of appetite, dizziness and nausea (p = 0.14–0.82). Four out of six RCTs (66.7%), showed that adjunctive rTMS was more efficacious over the control group in improving neurocognitive function (all p < 0.05). Conclusion Adjunctive rTMS appears to be a beneficial strategy in improving depressive symptoms and neurocognitive function in adolescents with FE-MDD. Higher quality RCTs with larger sample sizes and longer follow-up periods are warranted in the future.